Industrial organization a strategic approach - Church Jeffrey; Ware Roger (Boston McGraw-Hill, 2000)
Through an effective blend of analysis and examples this text integrates the game theory revolution with the traditional understanding of imperfectly competitive markets. The book's focus is on strategic competition and how firms can shelter their market
Keywords: Industrial organization